A Dramaturgical Analysis of Contingence in the Out of Orbit Festival 2021 - Shepherd, Diana (Architecture Image Studies, 2023)
The exploration of bodies and communication through the virtual medium was explored within this improvisational dance piece inspired by Cork, Ireland. Working in public spaces all over the world, the international set of dancers used an improvisational movement score to challenge and stretch the limits of communicating virtually and how it mirrors communication in the physical world. Taking into account body language as well and where it fits into both types of communication, the dancers worked with concepts of dissemination of information without speaking. Within the performance, the producer asked: How does the virtual stage allow for more malleable artistic processes through dance improvisation in a globalized context, while additionally recognizing the importance of the body in online communication? Through theories of globalization, programming, self-producing and risk, improvisation was explored and these findings led to conclusions on expanding the definition of ‘stage’, the importance of risk in performance and daily life and new questions on what is not seen and who does not do the seeing in improvisational performances.